2012
DOI: 10.1155/2012/104317
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline May Improve Language Developmental Trajectory in Young Children with Fragile X Syndrome: A Retrospective Chart Review

Abstract: Young children with fragile X syndrome (FXS) often experience anxiety, irritability, and hyperactivity related to sensory hyperarousal. However, there are no medication recommendations with documented efficacy for children under 5 years old of age with FXS. We examined data through a chart review for 45 children with FXS, 12–50 months old, using the Mullen Scales of Early Learning (MSEL) for baseline and longitudinal assessments. All children had clinical level of anxiety, language delays based on MSEL scores,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…Similarly, the consequences of FMRP expression depend on age (14). This is consistent with evidence from a retrospective chart review done by Winarni et al (65), which found that one to four year old children with FXS who received sertraline showed improved receptive and expressive language outcomes. It is critical that this therapeutic opportunity is further investigated with controlled trials, as it could lead to significant improvements in symptoms, cognition, and quality of life for patients with FXS.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Similarly, the consequences of FMRP expression depend on age (14). This is consistent with evidence from a retrospective chart review done by Winarni et al (65), which found that one to four year old children with FXS who received sertraline showed improved receptive and expressive language outcomes. It is critical that this therapeutic opportunity is further investigated with controlled trials, as it could lead to significant improvements in symptoms, cognition, and quality of life for patients with FXS.…”
Section: Resultssupporting
confidence: 91%
“…Clinical results and theoretical knowledge support the usefulness of SSRIs in treating patients with FXS (65). Sertraline may be relatively more effective than other SSRIs for this patient population.…”
Section: Unique Aspects Of Sertraline Among the Ssrismentioning
confidence: 69%
See 1 more Smart Citation
“…Such intervention is also recommended in young children with FXS both with and without autism or the PWP (29,30). A variety of medication use can be helpful for those with FXS both with and without the PWP including; stimulants which can help with attention and appetite; Selective Serotonin Reuptake Inhibitors (SSRIs), such as sertraline for anxiety (31); and atypical antipsychotics, such as aripiprazole to stabilize mood, improve autism, aggression and/or tantrums (6). However, aripiprazole can cause an increase in weight gain and particularly for those with a CYP2D6 polymorphism that can slow down the metabolism of aripiprazole (32).…”
Section: Treatmentmentioning
confidence: 99%
“…Genetic diagnosis shows that FXS is an X-linked genetic disorder that is characterized by behavioral problems and specific physical dysmorphisms (2). Child patients with FXS have ritualistic behaviors and social deficits and study has provided for early recognition and diagnosis for the children patients (3).…”
Section: Introductionmentioning
confidence: 99%